Risk Factors of Gestational Hypertension in Brebes Area - Naomi Christina Hutabarat; Ni Putu Dian Ayu Anggraeni (Alta Dharma Publisher, 2021)
Gestational hypertension is one of the three leading causes of maternal death after bleeding and infection. The study at to determine the risk factors among gestational hypertension. The analytic survey with a cross-sectional approach was applied in this study. The research was conducted from May 20th to June 28th, 2019, in the working area of ??three Public Health Centers in Brebes District. The research sample consisted of 80 samples (40 average pregnant women and 40 pregnant women with hypertension). The analysis in this research is descriptive. The results showed that pregnant women with a previous history of hypertension (OR 12.176; 95% CI 3.637-40.765) had 12.176 times the risk of developing gestational hypertension. Family history of hypertension (OR 4.333; 95% CI 1.271 – 14.777) had a 4.333 times risk of developing gestational hypertension. Other risk factors are third trimester gestational age and education with a p-value <0.05. No significant difference between primigravida and multigravida was found for gestational hypertension with a p-value > 0.05. This study can be used as a reference to reduce the incidence of gestational hypertension